PROSES PENGAMBILAN DATA DAN PEMANFAATAN GEOLISTRIK METODA 4-D UNTUK PEMETAAN GEOLOGI BAWAH PERMUKAAN - KUSWANTO, AGUS KUSWANTO (BPPT, 2018)
Geoelectricas as a method and tool for exploration has been started since the 1900s.The development of computer technology at this time makes the application of geoelectric method is now becoming more popular.The application of geoelectric methods usually for groundwater exploration but now widely used for mineral exploration and engineering geology.Today's inversion technique uses many geo-electric methods with 3-D configurations. The process of selecting the geoelectric method is important so that we can choose to use it. This research was conducted to utilize 4-D geoelectric method to identify object dynamics: waste seepage, soil density and groundwater. The application of this method (4-D) was identified to be used for monitoring and detecting potential flow of a fluid or sediment. Keyword : resistivity 3-D, resistivity 4-D, soil density, infiltration.